Effect of Chlorantraniliprole on Beneficial Fauna Associated with Soybean Cultivation - Carolina Sgarbi; Cecilia Beatriz Margaría; Elisabet Mónica Ricci (Ciencia y Tecnología Agropecuaria, 2023)
Using insecticides on soybean (Glycine max, L.) may induce lethal and sublethal effects on beneficial fauna associated with soybean cultivation. In Argentina, the application of pesticides in extensive and intensive crops for weed and insect control has increased by more than 400 % over the last 20 years. This study aimed to determine the effect of chlorantraniliprole applied under field conditions on predators and parasitoids associated with Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae). Phytophagous and predatory organisms were recorded in chlorantraniliprole-treated and untreated field plots during the 2014-2015 crop season. R. nu larvae were collected, individually placed in Petri dishes, and reared in a conditioned growth chamber until adult Lepidoptera or parasitoids appeared. Data were analyzed with the generalized linear mixed model. In untreated plots, the parasitoid Copidosoma sp. reduced the R. nu population growth curve below the economic injury level. In chlorantraniliprole-treated fields, differences before and after application were significant (p > 0.05), indicating that the insecticide affected predators (Araneidae, Syrphidae, Hemiptera) and parasitoids (Hymenoptera). Additionally, the Berger-Parker dominance index showed parasitoids were more sensitive to chlorantraniliprole than predators. Future research on selective insecticides with other action modes would be needed to evaluate sublethal effects on natural enemies.